Changes in Dry-Season Water Availability and Attributions in the Yellow River Basin, China - Zhao, Fubo; Ma, Shuai; Wu, Yiping (Frontiers in Environmental Science, 2021)
Global warming will significantly change patterns of precipitation (P) and evapotranspiration (E) and thus the surface water availability (P minus E, P–E). Changes in P–E will challenge freshwater supply, food security, and sustainability of the ecosystems. Therefore, understanding the spatiotemporal change in P–E and its drivers is key for water resources management. Here, we quantified the changes in water availability during the driest month of the year and identified its drivers in the Yellow River Basin (YRB), China, during 1982–2016). Our results showed that 89.6% of the YRB showed declining dry-season water availability in 2000–2016 compared with 1982–1999, although the total dry-season water resources (defined as the proportion of the sum of monthly P–E to the P) remained nearly unchanged due to the increased P. Changes in seasonal P and E contributed to 87.0% and 99.0% declines in dry-season water availability, respectively, demonstrating the key role of E in net seasonal water fluxes. Increased air temperature (41.8%), vegetation greening (30.8%), and vapor pressure deficit (19.2%) were the main factors driving changes in E in the YRB during the study period. Our study highlighted a drier dry season in the YRB during 1982—2016 and illustrated that climate and vegetation changes played important roles in driving changes in dry-season water availability. Seasonal water fluxes must be considered in future water resources management in the YRB, especially in the context of climate warming and revegetation programs.